The Family Background of 0' Level Learners and Its Impact on Their Learning of English in Nyakinoni Secondary School Kanungu District. - Night, Sarah (Kabale University, 2024)
This study investigated the family background of O'-level learners and its impact on their learning of English in Nyakinoni secondary school, Kanungu district. This study focused on the influences of family financial status, parents' education level, and family size on the students learning English in Nyakinoni secondary school, Kanungu district. The study employed a descriptive research design. The target population under study was 720 students in Nyakinoni secondary school and 720 parents. The study used a sample of 312 students and parents which were selected by Lise of a proportionate stratified random sampling method. Data was collected by use of a questionnaire for students and an interview schedule for parents. The data was analyzed quantitatively and qualitatively and presented using frequencies, Statistical Package for Social Sciences version 21 was used to aid in generating a summary of results which were represented in tabular form. The findings of the study showed that parents' education level and family financial status had a positive relationship with students' learning of English. An analysis revealed that 73% of the students' learning of English could be explained by the family's financial status. It was also concluded that in most big families the size of the family had no relationship with children's learning of English. The researcher recommends that for children to effectively learn English the family should have stable income froin whatever source, parents should endeavor to be academically sound if they have to influence their children's learning of English and family size should be average if the parents have to meet all the basics of their children for them to effectively learn English.